2017
DOI: 10.1002/chem.201701308
|View full text |Cite
|
Sign up to set email alerts
|

An Isolable Diboron‐Centered Diradical with a Triplet Ground State

Abstract: Two new diboranes, 2,6-bis(BMes )mesitylene (1) and 3,3'-bis(BMes )bimesitylene (3), were synthesized. Two-electron reduction of 1 with elemental potassium afforded the C-H activation product [(18-c-6)K(THF) ] ⋅2 bearing a BC four-membered ring as colorless crystals, whereas the reduction of 3 with potassium led to the isolation of [(18-c-6)K(THF) ] ⋅3 as dark blue crystals. Both reduction products were characterized by structural and spectroscopic methods. Electron paramagnetic resonance (EPR) spectroscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…All of them were formed by covalent bonding (Scheme ). The two boron radical centers in the four‐membered B 2 P 2 singlet diradical were coupled through space ( A ), while all others have the two boryl radical centers coupled by π ‐conjugated bridges ( B – H ) . Despite the fact that several boryl radical anions have been isolated, no formation of boryl diradicals through a self‐assembling approach has been observed.…”
Section: Methodsmentioning
confidence: 99%
“…All of them were formed by covalent bonding (Scheme ). The two boron radical centers in the four‐membered B 2 P 2 singlet diradical were coupled through space ( A ), while all others have the two boryl radical centers coupled by π ‐conjugated bridges ( B – H ) . Despite the fact that several boryl radical anions have been isolated, no formation of boryl diradicals through a self‐assembling approach has been observed.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al. reported that reduction of the phenylene‐bridged diborane 4 affords proton abstraction and B−H and C−B bond formations by a radical pathway . The known Al I compounds 5 and 6 react with the activated C−H bond of Cp*H to furnish Cp* hydride derivatives but do not react with C(sp 2 )−H bonds .…”
Section: Introductionmentioning
confidence: 99%
“… 19 (2) Wang et al observed hydrogen-atom abstraction from a H 3 C group with concomitant formation of B–H and B–C bonds when they reduced 2,6-bis(BMes 2 )mesitylene to its diradical state. 20 (3) Fontaine exploited an intramolecular deprotonation step on an FLP platform to establish an NCH 2 –B bond; subsequent H 2 liberation provided the necessary thermodynamic driving force. 21 …”
Section: Introductionmentioning
confidence: 99%